Descripciones para el buen gobierno y provecho de la tierra, vecinos e indios samarios : conocer las Provincias de Santa Marta a través de las Relaciones Geográficas de Indias (1577-1582) (2017)
This monograph belongs to the tradition of History of Hispanic American science and knowledge, and its role in the foundations of the Modern World. The aim of this text is to study the Relaciones Geográficas of the provinces of the Gobernación de Santa Marta, to understand the development of knowledge on the natural landscape and the populations of the Amerindians and Spaniards in Nuevo Reino de Granada during the late 16th century. To achieve this purpose, this text analyzes the articulation between imperial and local interests; the literate bureaucracy that formulated and answered those questionnaires; the purpose of "good government"; and the legitimization of some regional demands and requests. Straightaway, it examines how different fields of human social life and natural landscape are comprehended as knowledge and benefit objects: for example, land, weather, animals, plants, indigenous customs and the socioeconomic life of Spanish colonizers, all of them taking part in the peninsular worldview, and at the same time being questioned in their contact with New World cultures. The monograph also studies the necessary knowledge practices to affirm that nature and population are known, identifying some empirical practices as observation and inquiring; some cartographical and chorographical practices, as mapping; and some scriptural and writing practices, as description and comparison, partially linked to Rhetorical traditions. Finally, the role of the Relaciones Geográficas in studies of modern science and knowledge is considered, establishing some historiographical reflections on Modernity, based on the analysis of the selected cases of the Gobernación de Santa Marta.--Tomado del Formato de Documento de Grado.